Antagonistic pleiotropy can maintain fitness variation in annual plants. (8th November 2017) - Brown, K. E.; Kelly, J. K.
Abstract: Antagonistic pleiotropy (AP) is a genetic trade‐off between different fitness components. In annual plants, a trade‐off between days to flower (DTF) and reproductive capacity often determines how many individuals survive to flower in a short growing season, and also influences the seed set of survivors. We develop a model of viability and fecundity selection informed by many experiments on the yellow monkeyflower, Mimulus guttatus, but applicable to many annual species. A viability/fecundity trade‐off maintains stable polymorphism under surprisingly general conditions. We also introduce both spatial heterogeneity and temporal stochasticity in environmental parameters. Neither is necessary for polymorphism, but spatial heterogeneity allows polymorphism while also generating the often observed non‐negative correlations in fitness components.